Nutritional Care Management of a Pediatric Patient with Stage V Chronic Kidney Disease on Hemodialysis Complicated by Hypertension and Pulmonary Edema with a Differential Diagnosis of Rheumatic Heart Disease - Komang Windayani; Kiki Rizky Ananda; Wiwik Ekorinawati; Eka Rusliana; Laras Sekar Windaningrum (Journal of Global Nutrition, 2026)
Chronic Kidney Disease (CKD) stage V in pediatric patients requires renal replacement therapy such as hemodialysis and is often accompanied by complications including hypertension and cardiovascular disorders, such as suspected rheumatic heart disease (RHD). These conditions increase the risk of fluid overload, pulmonary edema, and nutritional problems, thus requiring comprehensive nutritional management. This study used a descriptive observational case study design conducted at Dr. Moewardi General Hospital, Surakarta. The subject was selected using purposive sampling based on the risk of malnutrition using the STRONG-kids screening form. Data were collected through interviews, medical records, anthropometric measurements, biochemical and clinical assessments, and a 24-hour food recall. Nutritional care was carried out using the standardized Nutrition Care Process, including assessment, diagnosis, intervention, education, and monitoring for three days. The subject was a 13-year-old pediatric patient with CKD undergoing hemodialysis, presenting with edema, hypertension, and suspected RHD. Dietary intake was inadequate (<70%). Anthropometric assessment based on Mid-Upper Arm Circumference (MUAC) indicated normal nutritional status despite the presence of edema. Biochemical examination showed anemia and increased creatinine and urea levels. Nutritional intervention showed an increasing trend in intake over three days, although energy and carbohydrate intake remained deficient. Clinical parameters, including blood pressure and respiratory rate, showed improvement, along with decreased creatinine and urea levels. Nutritional therapy in the form of a hemodialysis diet and low-sodium diet contributed to improved intake, fluid balance, and clinical outcomes. Sodium restriction played an important role in controlling blood pressure and preventing fluid overload, including the risk of pulmonary edema. Integrated nutritional management combined with hemodialysis improved intake, clinical condition, and biochemical parameters in pediatric CKD patients with hypertension and suspected RHD.